Where Do You Get Your Protein? Or: Biochemical Realization. (2nd August 2019) - Tahko, Tuomas E
Abstract: Biochemical kinds such as proteins pose interesting problems for philosophers of science, as they can be studied from the points of view of both biology and chemistry. The relationship between the biological functions of biochemical kinds and the microstructures that they are related to is the key question. This leads us to a more general discussion about ontological reductionism, microstructuralism, and multiple realization at the biology–chemistry interface. On the face of it, biochemical kinds seem to pose a challenge for ontological reductionism and hence motivate a dual theory of chemical and biological kinds, a type of pluralism about natural kinds. But it will be argued that the challenge, which is based on multiple realization, can be addressed. The upshot is that there are reasonable prospects for ontological reductionism about biochemical kinds, which corroborates natural kind monism. 1 Introduction 2 Functions: Aetiological or Goal-Directed? 3 Moonlighting and Multiple Determinations 4 The Powers-Based Subset Strategy 5 The Case of Haemoglobin 6 Haemoglobin and the Problem of Lower-Level Vengeance 7 Multiple Realization and (Higher-Order) Interest Relativeness 8 The Prospects for Ontological Reductionism